Determination of Optimal Diagnostic Cut-Offs for the Naval Medical Research Centre Scrub Typhus IgM ELISA in Chiang Rai, Thailand. - Phanichkrivalkosil, M; Tanganuchitcharnchai, A; Jintaworn, S; Kantipong, P; Laongnualpanich, A; Chierakul, W; Paris, D; Richards, A; Wangrangsimakul, T; Day, N; Blacksell, S (American Society of Troppical Medicine and Hygeine, 2019)
In this diagnostic accuracy study, we evaluated data from 135 febrile patients from Chiang Rai, to determine the optimal optical density (OD) cutoffs for an in-house scrub typhus IgM ELISA. Receiver operating characteristic curves were generated using a panel of reference assays, including an IgM immunofluorescence assay (IFA), PCR, in vitro isolation, presence of an eschar, or a combination of these. Altogether, 33 patients (24.4%) were diagnosed as having scrub typhus. Correlation between positivity by IFA and increasing OD values peaked at a cutoff of 2.0, whereas there was little association between positivity by culture or eschar with increasing ELISA cutoffs-cutoffs of 3.0 and 4.0 were demonstrated to be optimal for the total absorbance of the OD at dilutions 1:100, 1:400, 1:1,600, and 1:6,400, for admission and convalescent samples, respectively. The optimal cutoff at a 1:100 dilution was found to be between 1.85 and 2.22 for admission samples and convalescent-phase samples, respectively. Sensitivities for the cutoffs varied from 57.1% to 90.0% depending on the reference test and sample timing, whereas specificities ranged from 85.2% to 99.0%. We therefore recommend a cutoff of around 2.0, depending on the sensitivity and specificity desired in clinical or epidemiological settings. The results demonstrate the ELISA to be a valuable diagnostic tool, suitable for use in resource-limited endemic regions, especially when used in combination with other diagnostic modalities such as the presence of an eschar.